Behcet's disease and severe inflammatory reaction to 23-valent pneumococcal polysaccharide vaccine: a case report and review of literature. Issue 4 (November 2018) - Saeidinejad, MohammadMahdi; Kardash, Sally; Connell, Laura
Current European League Against Rheumatism guidelines strongly recommend considering the use of polysaccharide pneumococcal vaccine in all patients with autoimmune inflammatory rheumatic diseases. However, a previously published case series reports of reactions to 23-valent pneumococcal polysaccharide vaccine in patients with Behcet's disease. The purpose of this report is to present a similar case of a systemic adverse reaction in a patient with Behcet's disease to 23-valent pneumococcal polysaccharide vaccine.